Challenges in Providing Treatment of Severe Malaria Case in aDistrict Hospital of Remote Area in Indonesia - Priantono, Dimas; Purnama, Asep; Nelwan, Erni Juwita (Jurnal Penyakit Dalam Indonesia, 2017)
Severe Malaria is commonly found due to Plasmodium falciparum infection, which is causing high mortality in patient. A Severe case might be difficult to treat optimally in the remote settings area that could be due to lack in awareness of disease manifestation and inadequate diagnostic facilities. We report a case of Severe Malaria Falciparum infection, confirmed by blood smear examination of Plasmodium falciparum (Pf) parasites. Patient had received Artemicinin Based Combination Therapy (ACT), which consisted of dihydroartemisinin (DHA)-piperaquine and primaquine (PQ) with no clear clinical and microscopy improvement. The second line anti malaria consisted of quinine, doxycycline, and PQ was then initiated, showing clinical and microscopy responses.